Online Cognitive Behavior Therapy-based interventions for patients with anxiety symptoms in times of pandemic: an integrative review (Research, Society and Development, 2023)
The COVID-19 pandemic and social isolation triggered several problems, whether social, economic or health. Among these, we can highlight the increase in mental health conditions, due to anxiety, stress or symptoms associated with these. With this in mind, different strategies were used for the care and management of these cases, such as online Cognitive Behavioral Therapy - eTCC. Objective: To present an overview of eTCC-based interventions for patients with anxiety symptoms in times of pandemic. Method: searches were performed in the following databases: PubMed/MedLine, BVS and SciELO with the descriptors “COVID-19” or “sars-cov-2” and “anxiety” and “psychotherapy” or “cognitive behavior therapy” or “cognitive therapy” and “online” or “telecare” or “telemedicine”. Articles in any language, the last two years, in any design and related to the central theme were considered. Results: The search resulted in 204 articles related to the central theme, among these, 10 were selected for the composition of the study. The studies were mostly randomized clinical trials, with the main objective of analyzing the effectiveness of eTCC. Conclusion: It was possible to observe the effectiveness of eTCC when compared to other therapies, in addition to the reduction of associated symptoms, economic costs and greater population reach, with eTCC being a promising strategy for the coming years.